PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris Terhadap Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Muhammad Iswahyudi; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2017)
AbstractThe purpose of this research is 1) to know the influence of corporategovernance mechanism toward for corporate social responsibility, 2) to know theeffect of company size to corporate social responsibility, 3) to know the influenceof profitability to corporate social responsibility.The population used in this study are all manufacturing companies listedon the Indonesia Stock Exchange (BEI) in 2013-2015. Sample selection usingpurposive sampling. Based on the criteria, obtained 50 companies that becamethe sample in this study. The method used in this study using multiple linearregression method.Based on the results of the analysis can be put forward severalconclusions as follows: 1) T test results show that for corporate governancemechanism variable has no significant effect on firm value, company size has nosignificant effect on corporate social responsibility, and profitability (ROE)Significant to corporate social responsibility. 2) The result of f test shows thatcorporate governance mechanism, company size, profitability (ROE) andsimultaneously have significant influence to corporate social responsibility.Keywords: Corporate Governance Mechanism, Company Size, Profitability,Corporate Social Responsibility.